Risk of stroke in patients with congenital heart disease: a systematic review and meta-analysis - Ramez M. Odat; Muhammad Idrees; Hritvik Jain; Sakhr Alshwayyat; Husam Aldean H. Hussain; Basma Badrawy Khalefa; Ali O. Aldamen; Abdel Rahman K. Bani Yaseen; Bassel Alrabadi; Mohammad-Amer A. Tamimi; Ayham Mohammad Hussein; Hamdah Hanifa; et al. (BMC Neurology)
Abstract Background Patients with congenital heart disease (CHD) are more likely to experience ischemic and hemorrhagic stroke due to factors such as arrhythmias, residual shunts and related cardiovascular complications. However, guidelines for identifying CHD patients at the highest risk of stroke remain unclear. In this study, we aimed to evaluate the risk of developing stroke in patients with CHD. Methods A systematic literature search was performed on PubMed, Scopus, Cochrane, and Embase databases to retrieve studies that evaluated stroke risk in patients with CHD. Random effects model was used to pool the hazard ratios (HR) with 95% confidence intervals (CI). Subgroup analysis was conducted on age, type of stroke, type of study and region. Publication bias was assessed by Egger’s regression test. Statistical significance was set at p < 0.05. All the analysis was performed using R studio V4.3.1. Results Eleven studies (5,490,412 participants) were included in this systematic review and meta-analysis. Patients with CHD were at a higher risk of stroke [Pooled HR: 3.25; 95% CI: 2.25, 4.68; p < 0.01; I2: 100%] than the control group. In subgroup analysis, patients with CHD were at a higher risk of ischemic stroke [Pooled HR: 4.45; 95% CI: 2.24, 8.85; p < 0.01; I2: 100%] and hemorrhagic stroke [Pooled HR: 4.70; 95% CI: 1.70, 12.96; p < 0.01; I2: 99%] than the control group. Conclusion Our meta-analysis indicates a significantly increased stroke risk in patients with CHD. Subgroup analyses showed higher stroke risk in European regions compared to Asia and USA, and among adults compared to pediatric populations. Future studies should focus on addressing regional and data limitations to better inform clinical strategies for managing stroke risk in CHD patients. Graphical Abstract